Optimization of Water Source Management for the Community of Apuan Village, Susut District, Bangli Regency - Ni Made Puspasutari Ujianti; Ida Ayu Putu Widiati; Luh Putu Suryani; I Wayan Suambara (Fakultas Hukum, Universitas Warmadewa, 2022)
Apuan Village is one of the villages located in Susut District, Bangli Regency. The Apuan Village Government has received assistance from the Bangli Regency Government in the context of the construction of drinking water supply facilities which in its management are handed over to Apuan Village. In its development, the distribution of drinking water in Apuan Village has not been able to reach the entire community of Apuan Village, so a drinking water facility development program is needed. However, the program is constrained in terms of authority and funding. In fact, the results of the management of water sources for drinking water which are handled by Apuan Village, are fully intended for the benefit of the village community, so there is no availability of funds to support the program plan for the development of drinking water management facilities. The Apuan Village Government does not have the authority to carry out the water management development program, considering that there is no legal umbrella for the Apuan Village Government to run the drinking water management development program in Apuan Village. The solution to overcome partner problems is to provide legal assistance and counseling related to the legal form of the drinking water management development program and the realization of a harmonious working relationship in the development of drinking water management in Apuan Village.